2007
DOI: 10.5694/j.1326-5377.2007.tb00778.x
|View full text |Cite
|
Sign up to set email alerts
|

The increasing cost of the basic foods required to promote health in Queensland

Abstract: Objective: To assess changes in the cost and availability of a standard basket of healthy food items (the Healthy Food Access Basket [HFAB]) in Queensland over time. Design and participants: A series of four cross‐sectional surveys (in 1998, 2000, 2001 and 2004) describing the cost and availability of foods in the HFAB over time. In the latest survey, 97 Queensland food stores across the five Australian Bureau of Statistics remoteness categories were compared. Main outcome measures: Cost comparisons for HFAB i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 5 publications
1
82
0
1
Order By: Relevance
“…However these three communities represent the variation that exists in relation to size, remoteness and number of food businesses and services across remote Aboriginal communities. Similar nutrition profiles and socio-economic conditions and disparities in the cost of food exist across Aboriginal communities in remote Australia[4]; [6]. Applying this technique of optimisation modelling over a larger number of communities however is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However these three communities represent the variation that exists in relation to size, remoteness and number of food businesses and services across remote Aboriginal communities. Similar nutrition profiles and socio-economic conditions and disparities in the cost of food exist across Aboriginal communities in remote Australia[4]; [6]. Applying this technique of optimisation modelling over a larger number of communities however is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…High food costs and low socio-economic position are key determinants of this poor quality diet[3]. Surveys to assess the cost of a defined basket of foods in different states[4]; [5] and the Northern Territory (NT) of Australia[6] have consistently demonstrated relatively higher food costs outside major cities that increase with categories of remoteness[4]. The cost is 49% higher for remote NT communities compared to a provincial city supermarket[6].…”
Section: Introductionmentioning
confidence: 99%
“…Of the studies conducting a price comparison between store types, six studies found that larger grocery stores had cheaper prices for healthy food items compared to smaller grocery stores [9, 42, 44, 52, 53, 65] and three studies found that convenience stores and gas stations had higher prices compared to grocery and supermarkets [23, 56, 57] for healthy food items.…”
Section: Overall Food Availability In Storesmentioning
confidence: 99%
“…As in many other countries, Australian consumers have had to accommodate to increases in costs of basic food [1]. During the financial years 2007-2008 alone, overall food prices rose by 3.9%, while some basic food prices rose more sharply: cheese by 14.2%, milk by 12.1%, poultry by 11.0%, and bread by 6.8% [2].…”
Section: Introductionmentioning
confidence: 99%